Beyond the Classroom: Transformative Approaches in Learning Methods - Frans, Nofry; Wahani, Vera (Universitas Pahlawan Tuanku Tambusai, 2025)
Traditional classroom-based instruction has long dominated institutional learning paradigms; however, educational practices are increasingly shifting beyond structured settings to embrace more flexible and learner-centered approaches. This study aims to explore transformative learning strategies—specifically self-regulated learning (SRL), storytelling pedagogy, and gamified digital tools such as Duolingo—to enhance cognitive and linguistic development. Using a systematic literature review methodology, the study synthesizes theoretical perspectives and empirical findings from the past decade. The findings reveal that SRL fosters learner autonomy and metacognitive awareness, enabling students to take ownership of their learning processes. Storytelling pedagogy supports vocabulary retention and fluency by embedding language learning in meaningful, emotionally engaging contexts. Gamified digital platforms further enhance learner motivation and engagement through adaptive and interactive learning environments. These approaches collectively contribute to sustained proficiency and long-term retention. The study concludes that integrating these innovative, evidence-based strategies—supported by technology and experiential learning—represents a necessary evolution in modern pedagogy, requiring educators to rethink instructional design beyond the limits of the traditional classroom.